Analysis of the Implementation of Total Quality Management (TQM) through Competitive Advantage on Company Performance: Study in the Pharmaceutical Industry of PT Kimia Farma Tbk Indonesia - Sarin Sirait; Anisah, Hastin Umi (Open Access Indonesia Journal of Social Sciences, 2024)
In the competitive landscape of the Indonesian pharmaceutical industry, companies are required to continue to innovate and improve performance. Total quality management (TQM), a holistic management approach that focuses on continuous quality improvement, has been identified as a potential driver of corporate performance. However, the mechanism of how TQM influences performance, especially through competitive advantage, is still not fully understood in the context of the pharmaceutical industry. This research aims to fill this gap by investigating the mediating role of competitive advantage in the relationship between TQM implementation and company performance at PT Kimia Farma Tbk, one of the leading pharmaceutical companies in Indonesia. This research adopts a quantitative approach with a survey design. Data was collected from 128 employees of PT Kimia Farma Tbk who were randomly selected using a stratified random sampling technique. Data analysis was carried out using partial least squares structural equation modeling (PLS-SEM) with the help of SmartPLS software. The research results reveal that TQM has a positive and significant influence on competitive advantage and company performance. Furthermore, competitive advantage is proven to partially mediate the influence of TQM on company performance. These findings underline the important role of TQM in improving the performance of pharmaceutical companies through developing competitive advantage. The managerial implication of this research is that it is important for PT Kimia Farma Tbk and other pharmaceutical companies to continue to strengthen the implementation of TQM and strategically utilize the resulting competitive advantages to achieve superior performance in an increasingly competitive market.